RENDAHNYA LULUSAN SDN 21 BANYUASIN II MELANJUTKAN KE SMP SEDERAJAT DI DUSUN SUNGAI KELADI KECAMATAN BANYUASIN II - Riyanto, Tobing; Suryati, Suryati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to determine the extent to which remote communities in Sungai Keladi Hamlet looked at the importance of education and to find out what factors influenced the low interest in continuing education for remote children in Sungai Keladi Hamlet, Banyuasin District II. This research is a qualitative research. The sampling technique of the respondents used purposive sampling obtained by 30 respondents. This data collection uses the method of observation, interviews and documentation. The analysis used is descriptive. The results of this study indicate that: (1) The views of remote communities in Sungai Keladi Hamlet on the importance of education are still very low, this can be seen from the many children graduating from SDN 21 Banyuasin II who did not continue their education and drop out of school. (2) Factors that influence the low level of children in continuing education in Sungai Keladi Hamlet, Banyuasin II Subdistrict, namely (a) Factors in the low level of education of parents / guardians of students, (2) Lack of understanding of the importance of education (b) c) Distance factors for high school, and (d) Environmental factors.